2019
DOI: 10.1103/physrevlett.122.050401
|View full text |Cite
|
Sign up to set email alerts
|

Instability of Rotationally Tuned Dipolar Bose-Einstein Condensates

Abstract: The possibility of effectively inverting the sign of the dipole-dipole interaction, by fast rotation of the dipole polarization, is examined within a harmonically trapped dipolar Bose-Einstein condensate. Our analysis is based on the stationary states in the Thomas-Fermi limit, in the corotating frame, as well as direct numerical simulations in the Thomas-Fermi regime, explicitly accounting for the rotating polarization. The condensate is found to be inherently unstable due to the dynamical instability of coll… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 52 publications
(93 reference statements)
2
45
0
Order By: Relevance
“…While Branch III terminates at Ω = ω ⊥ with α → −ω ⊥ as Ω → ω ⊥ , the overcritical Branch II persists for Ω → ∞. Though we do not consider this limit, it has been found that Branch II monotonically approaches the limit α → 0 − as Ω → ∞ [62]. In Fig.…”
Section: Stationary Solutions Of the Thomas-fermi Problemmentioning
confidence: 89%
See 2 more Smart Citations
“…While Branch III terminates at Ω = ω ⊥ with α → −ω ⊥ as Ω → ω ⊥ , the overcritical Branch II persists for Ω → ∞. Though we do not consider this limit, it has been found that Branch II monotonically approaches the limit α → 0 − as Ω → ∞ [62]. In Fig.…”
Section: Stationary Solutions Of the Thomas-fermi Problemmentioning
confidence: 89%
“…In Ref. [62], it was found that a bifurcation exists in this system at a given rotation frequency Ω b , a quantity that is dependent on dd and γ, at which the number of stationary solutions increases from 1 to 3 [62]. When dd = 0, the bifurcation diagram is symmetric about the Ω axis and two additional symmetric branches emerge when Ω = ω ⊥ √ 2.…”
Section: Stationary Solutions Of the Thomas-fermi Problemmentioning
confidence: 94%
See 1 more Smart Citation
“…We have examined the properties of the resulting state in dynamical simulations to verify the effects of the tuned interactions, and the ramp time scale needed to avoid excessively exciting collective modes. We observe the dynamic instabilities predicted by Prasad et al [12], and find that the kinetic energy provides a useful observable of the instability and allows us to identify an instability time. Our results indicate that the time scale of the instabilities is sensitive to the rotation frequency of the magnetic field, and we find that in many cases the instability can be delayed for sufficiently high frequency.…”
Section: Discussionmentioning
confidence: 67%
“…Initially E K displays oscillatory dynamics at a frequency comparable to the trap frequency, arising from the collective modes excited. However, at later times E K suddenly starts rapid growth, corresponding to the instability identified in [12] and marking where the condensate begins to heat. For the Ω/2π = 2 kHz case, corresponding to the same simulation shown in Fig.…”
Section: Resultsmentioning
confidence: 98%